Public opinion on sentencing and parole in Australia - Bartels, Lorana (Probation journal, 2018)
Australia has nine different legislative regimes for sentencing and parole, as well as eight prison regimes; it has therefore been described as an ideal penal laboratory. This paper presents an overview of the extensive body of recent Australian research on public opinion on sentencing and, more recently, parole. The discussion on parole is situated in the context of an analysis of the legislative and policy landscape, which has undergone significant changes in recent years. The paper concludes with some comments on future research directions in relation to Australian public opinion on parole.